USM FUTURE DENTISTS SHINE AT NATIONAL DENTAL INTERVARSITY SPORTS CARNIVAL - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
KUBANG KERIAN, KELANTAN, 1 April 2017 Students from the Universiti Sains Malaysia (USM) School of Dental Sciences (PPSG) today made a clean sweep to become the overall champion in the National Dental Intervarsity Sports Carnival held at the USM Health Campus here today.